Les Elections Ã l’Assemblée de la Polynésie Française - Guiselin, Emmanuel-Pie (Victoria University of Wellington Law Review, 2004)
The law of 27 February 2004 about the new status of French Polynesia modifies two important points of the electoral rules for appointing the islands’ governing assembly. This law increases the number of constituencies from five to six and has a new method of allocating seats. Most importantly, the law creates a new voting system with a mixture of proportional and first-past-the-post representation. The size of the first-past-the-post representation, one third of the seats, makes this change very important.